Ultra-high-performance Liquid Chromatography as an Assay Method for the Investigation of Conditions of Captopril Extraction by Organic Solvents - Logoyda, Liliya (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: In recent years, the principle and theory behind solvent extraction has gained wide acceptance as one of the new tools of modern pharmaceutical analysis. Analytical chemists have been using solvent extraction in the laboratory for many years for extracting molecular species from aqueous solutions by organic solvents. However, the requirements and objectives of an analytical procedure are quite different from those of a profit producing mill flow sheet. Depending on the nature, aggregate state, sample concentration and method of analysis, and various sampling procedures are used: Moisture removal, grinding, decomposition, dissolution, melting, elution, removal of the matrix, dilution, concentration, etc. The objective of this research was to select the optimal conditions for the extraction for captopril by organic solvents from water solutions in dependence on pH solutions. Materials and Methods: The chromatographic analysis of captopril performed on liquid chromatography ACQUITY Arc system. Results: The obtained data testify that the optimal solvents for the extraction of captopril in the process of separating it from objects of biological origin are chloroform and methylene chloride. The amount of substance released by chloroform is 91.48% (at pH 1), methylene chloride is 97.97% (at pH 1), and hexane is 69.65% (at pH 2). Conclusion: The extraction of captopril by organic solvents from water solutions in dependence on pH solutions has been conducted. As a result of studies, we have found that the optimal extragent is methylene chloride, which is extracted at pH 1–97.97% and chloroform is extracted at pH 1–91.48%.